MARKETING INFORMATION AND THE ROLE OF THE ACTOR IN THE ADVANCEMENT BY INSTITUTIONS OF INFORMATION (International Journal of Engineering Sciences & Management Research, 2026)
The study seeks to clarify the most important dimensions and forms of marketing information, its characteristics and the appropriate ones for marketing, the content of its marketing activity, the briefing of the means to ensure the success of its marketing, and the most important methods that informational institutions pursue in their marketing plans, as well as to identify the obstacles of marketing information. The study adopted a documentary approach to collect information from various electronic and paper sources, as it came out with a set of conclusions, the most important of which are: 1. Information, resources, and planning play a prominent role in the strategic advancement of marketing in information enterprises. 2. Marketing information is based on cultural, political, innate, and financial considerations in promoting marketing. As for the most important recommendations, they were the following: 1. Developing appropriate plans to ensure the advancement of information institutions in the marketing of information. 2. Our informational institutions should take the initiative and forcefully to enter the market of competition with other Arab and international institutions.